Is it believable when it's scientific? How scientific discourse style influences laypeople's resolution of conflicts. Issue 1 (3rd September 2014) - Bromme, Rainer; Scharrer, Lisa; Stadtler, Marc; Hömberg, Johanna; Torspecken, Ronja
Abstract Scientific texts are a genre in which adherence to specific discourse conventions allows for conclusions on the scientific integrity of the information and thus on its validity. This study examines whether genre‐typical features of scientific discourse influence how laypeople handle conflicting science‐based knowledge claims. In two experiments with a total of N = 120 participants we investigated to what extent laypeople take into account such features when judging the "scientificness" and credibility of conflicting knowledge claims about medical issues and issues related to climate change and when determining their personal agreement with conflicting claims. Results showed that laypeople use genre‐typical discourse features to evaluate the scientificness and credibility of conflicting science‐based information. However, depending on the scientific topic, they appear to distinguish between what they judge to be credible and what they personally believe to be true. Educational implications of the findings are discussed. © 2014 Wiley Periodicals, Inc. J Res Sci Teach 52: 36–57, 2015